Pengembangan Bahan Ajar Matemtika dengan Bantuan Aplikasi Geogebra pada Materi Bangun Ruang di SMP - Lestari, Novia; Hartono, Hartono; Suhari, Suhari (Publikasi Indonesia, 2025)
Mathematics learning is often perceived as difficult by students due to its abstract nature and the need for strong logical thinking and visualization skills, particularly in geometry topics such as solid shapes. Many students struggle to grasp three-dimensional concepts through verbal explanations or static textbook images alone. Therefore, there is a need for innovative teaching materials that can bridge conceptual understanding in a more concrete and engaging way. This study aims to develop mathematics teaching materials using the GeoGebra application for the topic of solid geometry to enhance student engagement in the learning process. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The validation process involved experts in subject matter, design, and media. The research subjects consisted of 30 eighth-grade students and a mathematics teacher at SMP Negeri 1 Uwapa. Two instruments were used: expert validation questionnaires and practicality questionnaires for both teachers and students. All instruments utilized a Likert scale for quantitative data analysis regarding the validity and practicality of the teaching materials. Based on the research findings, the developed mathematics teaching materials received validation scores of 94.40% from subject matter experts, 97.25% from design experts, and 84.00% from media experts, classifying them as highly valid. After validation, the materials were tested on students, yielding practicality scores of 94.71% for individual trials, 94.47% for small group trials, and 92.09% for large group trials, categorizing them as highly practical.